Examining the interlocking of tourism editorial boards. (April 2021) - Lockstone-Binney, Leonie; Ong, Faith; Mair, Judith
Abstract: This mixed-methods study examines the membership composition and concentration of the top 20 tourism journal editorial boards over time. Support was found for the emergent phenomenon of "interlocking editorship" (Baccini & Barabesi, 2010) explaining the concentrated structural properties of tourism journal editorial boards. Overwhelmingly, the boards sampled at two time points were found to be highly concentrated and homogenous, dominated in the majority by males and professorial level appointments. Contextualising these findings, the views of senior journal editors were sought in a qualitative study. For this cohort, interlocking editorship was not viewed as a significant challenge to knowledge production relative to other more pressing issues. Stemming from this longitudinal investigation that evidences interlocking editorship as affecting the structural properties of tourism editorial boards, a research agenda is proposed to advance understanding of the role and composition of tourism editorial boards. Highlights: The membership of tourism's top journal editorial boards is highly concentrated. It is also homogenous with males and professorial appointments dominating. The study evidences interlocking editorship with 100 interlocked individuals holding 35% of all editorial board positions. Greater diversity, transparency and accountability are needed for editorial appointments.